Żywienie dzieci z dysfunkcjami neurologicznymi - Kasica-Bańkowska, Katarzyna (Logopedia Silesiana, 2012)
Nutrition of neurologically impaired children Energy needs among neurologically impaired children are difficult to define, so malnutrition or overnutrition are common. Nutritional support should be integral part of therapy reducing morbidity and improving rehabilitation effects. Considering multidisciplinary team working with neurologically impaired children we should always remember about improving oromotor dysfunction and nutritional intervention.